Exploration of Bioengineered Scaffolds Composed of Thermo-Responsive Polymers for Drug Delivery in Wound Healing - Castillo, Luis (2021)
Se seleccionó la licencia Creative Commons para este envío. El documento trae lo siguiente: Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/4.0/). (En caso de duda consultar a Meilyn Garro).